Anti-Inflammatory Effects of Huangqin Decoction on Dextran Sulfate Sodium-Induced Ulcerative Colitis in Mice Through Regulation of the Gut Microbiota and Suppression of the Ras-PI3K-Akt-HIF-1α and NF-κB Pathways - Li, Min-yao; Luo, Hui-juan; Wu, Xue; Liu, Yu-hong; Gan, Yu-xuan; Xu, Nan; Zhang, Yao-min; Zhang, Shu-hua; Zhou, Chang-lin; Su, Zi-ren; Huang, Xiao-qi; Zheng, Xue-bao (Frontiers in Pharmacology, 2020)
Abstract Objective Huangqin Decoction (HQD), a classical traditional Chinese medicinal formula, has been commonly used to treat gastrointestinal diseases over thousands of years. We investigated the anti-inflammatory effects of HQD on dextran sulfate sodium (DSS)-induced colitis and underlying mechanisms involved. Methods The experimental mice with 3% DSS were given HQD (2.275g/kg, 4.55g/kg and 9.1g/kg) and Mesalazine (ME, 200 mg/kg) via oral administration for 7 days. The body weight loss, disease activity index (DAI), colon length, histological analysis and levels of inflammatory cytokines were determined to evaluate the effects of HQD on colitis. The effects of HQD on Ras-PI3K-Akt-HIF-1α and nuclear factor-kappa B (NF-κB) pathways were evaluated by western blot analysis. In addition, the gut microbiota was characterized by high-throughput Illumina MiSeq sequencing. Results The results revealed that HQD significantly ameliorated the body weight loss and DAI, restored the colon length and improved the intestinal epithelial cell barrier in DSS-induced colitis. The decreased mRNA expression levels of inflammatory mediators were observed after HQD treatment. Besides, the activation of Ras-PI3K-Akt-HIF-1α pathway and NF-κB pathway were significantly inhibited by HQD. Furthermore, HQD recovered the diversity of gut microbiota and regulated the gut microbiota. Conclusions HQD ameliorates DSS-induced colitis by regulating the gut microbiota, suppressing Ras-PI3K-Akt-HIF-1α pathway and downstream NF-κB pathway. Our investigation provides experimental evidences that HQD is a potential candidate in treatment of UC.